Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 41. Beitrag. Diptera: Rhagionidae. - Rozkošny, Rudolf; Spitzer, Karel (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The present paper evaluates the material on the family Rhagionidae collected in the expedition to Albania by Deutsches Entomologisches Institut and supplemented by the findings of J. Moucha’s tour of Albania. The material under investigation consisted of 20 specimens of 5 species, two of which were new in Albania. Together with previous findings there are now 8 species of Rhagionidae known from Albania. The conclusion gives an historical survey of the study of the Balkan population of this family and a table of its distribution.